The clinical outcomes of open reduction and internal fixation for Mason–Johnston type IV fractures of the radial head - Liu, Guanyi; Li, Qing; Xu, Ding; Zhang, Yong; Li, Ming; Zhang, Long (Frontiers in Surgery, 2025)
BackgroundThe treatment of displaced or comminuted Mason–Johnston type IV radial head fractures is challenging. These fractures often involve complex injuries to the ligaments surrounding the radial head, necessitating careful consideration of treatment strategies that prioritize ligament repair while preserving the integrity of the radial head whenever feasible. The primary objective of this study was to assess the clinical outcomes of open reduction and internal fixation (ORIF) in managing complex radial head fractures associated with transolecranon fractures, Monteggia fractures, and terrible triad injuries.MethodsBetween June 2015 and July 2019, twenty patients who underwent ORIF using screws, with or without mini plates, were retrospectively included in the current study to assess the outcomes for Mason–Johnston type IV fractures of the radial head. Based on the initial Mason classification, fourteen fractures were classified as Mason type II, while six were classified as type III. Among these patients, fourteen had terrible triad elbow injuries, three presented with transolecranon fracture and elbow dislocation, two with Monteggia fractures of Bado type II, and one with concomitant fracture of the radial head and elbow dislocation. Both clinical and radiographic evaluations were conducted.ResultsThe average duration of follow-up was 31 months, with a range of 24–40 months, and all patients achieved union without any evidence of postsurgical ligamentous instability or failure of internal fixation. The average range of motion for the affected elbow was 136° ± 6° of flexion, 12° ± 6° of extension, 74° ± 10° of pronation, and 67° ± 9° of supination, resulting in a flexion-extension arc of 123° ± 6° and a pronosupination arc of 142° ± 8°. The Broberg and Morrey clinical score averaged 88 ± 8 (range 75–100), with excellent outcomes observed in six patients, good outcomes in ten patients, and fair outcomes in four patients. Three out of 20 patients (15%) exhibited periarticular ossification.ConclusionThe results of the current study suggest that satisfactory elbow function can be achieved following ORIF for Mason–Johnston type IV fractures of the radial head.